SHLP6: a novel NLRP3 and Cav1 modulating agent in Cu-induced oxidative stress and neurodegeneration - H. Thamarai Kannan; Suganiya Umapathy; Ieshita Pan (Frontiers in Molecular Neuroscience)
IntroductionCopper sulfate exposure induces oxidative stress by triggering excessive reactive oxygen species (ROS) production, leading to inflammatory responses, neuroinflammation, and cellular dysfunction. Small humanin-like peptide-6 (SHLP-6), a mitochondria-derived peptide with anti-aging and anti-cancer properties, has not been explored for its protective effects against copper sulfate toxicity. This study investigates the antioxidant, anti-inflammatory, and neuroprotective potential of SHLP-6 in zebrafish larvae exposed to copper sulfate.MethodsZebrafish larvae were exposed to copper sulfate and treated with SHLP-6 at concentrations ranging from 10 to 50 μg/mL. ROS-scavenging activity was assessed using in vitro assays, and enzymatic antioxidant markers, lipid peroxidation, nitric oxide levels, acetylcholine esterase (AChE) activity, and locomotor behavior were evaluated. Additionally, gene expression analysis was performed for inflammatory and antioxidant markers.ResultsTreatment with SHLP-6 at 40 μg/mL significantly reduced malformations, improved heart rate (178 bpm), and increased survival rates (85%) in zebrafish larvae. The highest ROS inhibition was observed at 58.7% and 74.3%, while antioxidant enzyme activity was enhanced, with superoxide dismutase (68.3 U/mg), catalase (82.40 U/mg), and reduced glutathione (79.3 U/mg). Lipid peroxidation and nitric oxide levels decreased to 3.86 and 3.41 U/mg, respectively. SHLP-6 improved AChE levels (78.3 U/mg) and locomotor activity (43.53 m distance travelled).DiscussionSHLP-6 upregulated TNF-α (2.16-fold), NLRP3 (1.78-fold), and COX-2 (0.705-fold), while increasing IL-10 (1.84-fold), suggesting neuroinflammation modulation. Antioxidant gene expression (SOD, CAT, GST, and GSH) was significantly upregulated. These findings indicate SHLP-6’s potential as a neuroprotective and antioxidant agent against copper sulfate-induced toxicity.